Estudo comparativo entre interfaces hipertextuais de softwares para a representação do conhecimento - Marcel Ferrante Silva (2007)
Interdisciplinary study aiming at analyzing hypertextual interfaces developed in others fields like Computer Science viewed through the theories of Information Science. It analyses the potential of knowledge representation and browsing of software hypertextual interfaces to construct hierarchy diagrams, conceptual maps and hyperbolic maps. The proposed parameters to analyze the conceptual representation capacity are inspired in theories and methodologies of Science Information field: the Faceted Classification Theory; the Concept Theory; the standard ISO 2788 for monolingual thesaurus; and the standard ISO 704 for the terminology practice. As far as the browsing capacity, available resources were evaluated in order to facilitate the navigation in concept systems. This study also compares these types of hypertextual interfaces: hierarchical diagrams, conceptual maps and hyperbolic maps, highlighting the advantages and disadvantages in the each mentioned application. The study may serve as a starting point for system information architects in the choice of better interfaces to be used in their projects or by the designers of these interfaces in the development of new hybrid interfaces. The proposed principles could possibly be used to analyze others hypertextual interfaces.